FMR1: A gene with three faces - Oostra, Ben A; Willemsen, Rob (Biochimica et biophysica acta, 2009)
The FMR1 gene is involved in three different syndromes, the fragile X syndrome (FXS), premature ovarian insufficiency (POI) and the fragile X-associated tremor/ataxia syndrome (FXTAS) at older age. Fragile X syndrome is caused by an expansion of a CGG repeat above 200 units in the FMR1 gene resulting in the absence of the FMR1 mRNA and protein. The FMR1 protein is proposed to act as a regulator of mRNA transport and of translation of target mRNAs at the synapse. FXS is seen as a loss of function disorder. POI and FXTAS are found in individuals with an expanded repeat between 50 and 200 CGGs and are associated with increased FMR1 mRNA levels. The presence of elevated FMR1 mRNA in FXTAS suggests that FXTAS may represent a toxic RNA gain-of-function effect. The molecular basis of POI is yet unknown. The role of the FMR1 gene in these disorders is discussed.